Interpretation of Cone Penetration Test Data of an Embankment for Coupled Numerical Modeling - Mohammad Nurul Islam; Carthigesu T. Gnanendran; Siva T. Sivakumar (Applied Mechanics, 2021)
The Nerang Broadbeach Roadway (NBR) embankment in Australia is founded on soft clay deposits. The embankment sections were preloaded and surcharged-preloaded to limit the post-construction deformation and to avoid stability failure. In this paper, we discuss the NBR embankment’s geology, geotechnical properties of the subsurface, and long-term field monitoring data from settlement plates and piezometers. We demonstrate a comparison of cone penetration test (CPT) and piezo cone dissipation test (CPT-u) interpreted geotechnical properties and the NBR embankment’s foundation stratification with laboratory and field measured data. We also developed two elasto-viscoplastic (EVP) models for long-term performance prediction of the NBR embankment. In this regard, we considered both the associated and the non-associated flow rule in the EVP model formulation to assess the flow rule effect of soft clay. We also compared EVP model predictions with the Modified Cam Clay (MCC) model to evaluate the effect of viscous behavior of natural Estuarine clay. Both EVP models require six parameters, and five of them are similar to the MCC model. We used the secondary compression index of clay in the EVP model formulations to include the viscous response of clay. We obtained numerical models’ parameters from laboratory tests and interpretation of CPT and CPTu data. We observed that the EVP models predicted well compared with the MCC model because of the inclusion of soft clay’s viscosity in the EVP models. Moreover, the flow rule effect in the embankment’s performance predictions was noticeable. The non-associated flow rule EVP model predicted the field monitoring settlement and pore pressure better compared to the MCC model and the associated flow EVP model.